Subcultural theories - Gehring, Krista S. (CrimComics, 2019)
"CrimComics offers a new way to approach criminological theory by engaging students with impactful, highly visual illustrated texts. Each CrimComics Issue traces the development of the theory--placing it in social and political context--and demonstrates its application to the real world. The last page of each Issue features review questions and key terms. Issue 6, Subcultural Theories, introduces students to theories that emerged after WWII that sought to explain delinquent subcultures found among lower-class youth, particularly juvenile gangs."--